2018
DOI: 10.1177/1049732318789897
|View full text |Cite
|
Sign up to set email alerts
|

Building a Grounded Theory of Engagement in Mindfulness-Based Group Therapy for Distressing Voices

Abstract: Mindfulness based group therapy shows promise as a treatment for distressing voice-hearing.However, fostering engagement in groups can be challenging, and no theory of engagement in group therapy for distressing voices exists to guide practice or research. This study employed Grounded Theory Method to build a theory of engagement in mindfulness based groups for distressing voices. Ten service-users and three therapists were interviewed about their experiences of such groups. The model that emerged involves a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Participants mostly described ‘everyday’ barriers to home practice, such as children being at home, or noise coming from the street. This fits with previous qualitative studies in psychosis which mention noisy home environments, or external interruptions, as barriers to home practice [ 18 , 35 ]. Furthermore, our participants reflected on the role of the ‘internal’ environment, given how mindfulness involves turning towards what is present; therefore it is challenging to practice when this involves coming into contact with unwanted emotional states, although arguably this is when mindfulness skills can be honed most effectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Participants mostly described ‘everyday’ barriers to home practice, such as children being at home, or noise coming from the street. This fits with previous qualitative studies in psychosis which mention noisy home environments, or external interruptions, as barriers to home practice [ 18 , 35 ]. Furthermore, our participants reflected on the role of the ‘internal’ environment, given how mindfulness involves turning towards what is present; therefore it is challenging to practice when this involves coming into contact with unwanted emotional states, although arguably this is when mindfulness skills can be honed most effectively.…”
Section: Discussionsupporting
confidence: 89%
“…Similar themes were reported by McHale et al in terms of successful completion of home practice being contingent on the ‘right’ conditions (e.g. it being easier when feeling relaxed, and when the home environment was quiet vs. feeling agitated, and/or there being noise around at home) [ 35 ]. Some participants in an inpatient study spontaneously reported practising between sessions, and intending to carry this on at home after discharge as it had been beneficial for them: “well it’s just got me through so much, you know?…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In order to maximize both benefits for patients and added value, patients need to attend group PBCT sessions regularly. However, some patients have to overcome many barriers and challenges when trying to complete the 12 sessions (McHale et al, 2018). A minimum effective dose of group PBCT, or therapy completion, is considered to be attendance to at least eight out of 12 sessions (Chadwick et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This lends support to the importance of maintaining face‐to face interactions alongside digital technology. The benefits of universality (i.e., recognizing that others share similar problems) is a finding consistently reported in the literature for psychosis‐spectrum clients (McHale et al, 2018; McLeod et al, 2007; Ngo Nkouth et al, 2010), and is one of the key therapeutic‐factors of group interventions posited by Yalom and Leszcz (2005). This supports group therapy as a delivery modality, conferring benefits that are unlikely to be gained from individual work.…”
Section: Discussionmentioning
confidence: 75%